Nanozymes-recent development and biomedical applications - Ren, Xiangyi; Chen, Dongxu; Wang, Yan; Li, Huifang; Zhang, Yabing; Chen, Hongying; Li, Xi; Huo, Minfeng (Journal of nanobiotechnology, 2022)
Nanozyme is a series of nanomaterials with enzyme-mimetic activities that can proceed with the catalytic reactions of natural enzymes. In the field of biomedicine, nanozymes are capturing tremendous attention due to their high stability and low cost. Enzyme-mimetic activities of nanozymes can be regulated by multiple factors, such as the chemical state of metal ion, pH, hydrogen peroxide (H 2 O 2 ), and glutathione (GSH) level, presenting great promise for biomedical applications. Over the past decade, multi-functional nanozymes have been developed for various biomedical applications. To promote the understandings of nanozymes and the development of novel and multifunctional nanozymes, we herein provide a comprehensive review of the nanozymes and their applications in the biomedical field. Nanozymes with versatile enzyme-like properties are briefly overviewed, and their mechanism and application are discussed to provide understandings for future research. Finally, underlying challenges and prospects of nanozymes in the biomedical frontier are discussed in this review. Graphical Abstract